Bibliometric analysis and evidence of clinical efficacy and safety of digital pills - Litvinova, Olena; Klager, Elisabeth; Yeung, Andy Wai Kan; Tzvetkov, Nikolay T.; Kimberger, Oliver; Kletecka-Pulker, Maria; Willschke, Harald; Atanasov, Atanas G. (Frontiers in Pharmacology, 2023)
Objectives: Information technologies are one of the most important components of the healthcare system. The aim of the work was a bibliometric analysis of clinical studies of digital pills with ingestible sensors and an assessment of the level of evidence of their effectiveness, safety, and prospects for the future. Materials and Methods: The studies were conducted using online databases such as ClinicalTrials.gov and Dimensions for the period 2012–2022 (the first half of the year). The VOSviewer tool for building and visualizing bibliometric networks was used. Results: Bibliometric analysis of the scientific literature revealed that over the past 10 years, the number of publications about digital pills with ingestible sensors has noticeably increased, which indicates the increasing importance of this field of knowledge. The leading positions in this area are occupied by scientists from the USA, the United Kingdom, and India. The 4 main clusters of digital pill studies were highlighted and visualized: efficacy and safety analysis for serious mental disorders; treatment and costs of tuberculosis therapy and COVID-19; features of the treatment of diabetes, cardiovascular diseases, and AIDS; and usage monitoring. Nevertheless, the effects of digital pills have not yet been fully studied. Additional randomized controlled clinical trials and meta-analyses are necessary for a high level (I level) of evidence for therapeutic investigations. Conclusion: Further study, clinical testing, and the implementation into the practice of new effective and safe digital pills for pharmacotherapy will continue to be important priority areas of modern medicine.